(untitled) (Bangladesh Journal of Anatomy, 2010)
Context: Stature is the height of the person in the upright posture. It is an important measure of physical identity. Interrelationships among different body measurements may be used to estimate one from another in case of missing body parts. As any part of the human skeleton can be found as the evidences, there arise a need to investigate whether there is any possible significant correlation between stature and any parts in human body. Garos, our study subject living in Bangladesh are usually recognized as an ethnic community, they have a separate identity and their physical appearance is distinctive to some extent. The present study was conducted with the intention to establish ethnic specific anthropometric data for the Bangladeshi Garo tribal populations and also to determine whether there is any correlation between the measured values of the stature and the physically measured cranial variables, to estimate (using respective multiplication factor) the stature from the physically derived cranial measurements and to assess the effectiveness of such estimation. Study design: The study was an observational, cross-sectional and descriptive in nature with some analytical components. Study settings and study period: The study was carried out in Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, during the session of January to December 2008. Selections of the subjects: A total number of one hundred Garo female subjects were included from Dhaka city and Mymensingh district. Methods: Cranial dimension such as head circumference, head length and stature were measured using a measuring tape, spreading caliper, steel plate and steel tape. Results: Head circumference showed significant positive correlation with stature but head length did not reach statistically significant level with stature. No significant difference was found between the ‘measured’ and ‘estimated’ stature for head circumference and head length. Key words: Anthropometry; stature; correlation; head circumference; head length DOI: 10.3329/bja.v7i2.6096 Bangladesh Journal of Anatomy July 2009, Vol. 7 No. 2 pp. 101-104